2019
DOI: 10.1111/adb.12751
|View full text |Cite
|
Sign up to set email alerts
|

Respective influence of current alcohol consumption and duration of heavy drinking on brain morphological alterations in alcohol use disorder

Abstract: Numerous studies have explored the morphological differences of the brain between subjects with alcohol use disorder (AUD) and control subjects, but very few have investigated the impact of the duration of alcohol use disorder (DAD) and current level of alcohol consumption (CAC) within AUD subjects using magnetic resonance imaging (MRI). We compared the morphological MRI of 44 controls and 66 AUD subjects, recruited at the end of a detoxification program. Additional analyses within the AUD group determined whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Widespread reductions in GMV have been broadly documented in association with chronic alcohol use. Consistent with much previous literature, we found that, relative to controls, individuals with AUD had lower GMV in the ventromedial and orbitofrontal cortices, the anterior cingulate cortex, the bilateral insula, the DLPFC, and the primary motor cortex (Cardenas et al, 2007; Chanraud et al, 2007, 2009; Demirakca et al, 2011; Durazzo & Meyerhoff, 2020; Harding et al, 1996; Jang et al, 2007; Rolland et al, 2020; Segobin et al, 2014; Yang et al, 2016; Zou et al, 2018). Here, we extend the existing literature by quantifying GMV within three discrete noninvasive brain stimulation treatment targets for AUD: the left frontal pole, the left DLPFC, and the left motor cortex.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Widespread reductions in GMV have been broadly documented in association with chronic alcohol use. Consistent with much previous literature, we found that, relative to controls, individuals with AUD had lower GMV in the ventromedial and orbitofrontal cortices, the anterior cingulate cortex, the bilateral insula, the DLPFC, and the primary motor cortex (Cardenas et al, 2007; Chanraud et al, 2007, 2009; Demirakca et al, 2011; Durazzo & Meyerhoff, 2020; Harding et al, 1996; Jang et al, 2007; Rolland et al, 2020; Segobin et al, 2014; Yang et al, 2016; Zou et al, 2018). Here, we extend the existing literature by quantifying GMV within three discrete noninvasive brain stimulation treatment targets for AUD: the left frontal pole, the left DLPFC, and the left motor cortex.…”
Section: Discussionsupporting
confidence: 90%
“…Cortical atrophy following chronic alcohol use is likely one of the most documented and critical features that influences TMS efficacy in these individuals (Cardenas et al, 2007; Durazzo et al, 2011; Rolland et al, 2020; Yang et al, 2016; Zahr & Pfefferbaum, 2017). Focal reductions in gray matter volume (GMV) within the frontal lobe (containing the frontal pole and DLPFC) are consistently reported in association with chronic AUD (Cardenas et al, 2007; Chanraud et al, 2007, 2009; Demirakca et al, 2011; Jang et al, 2007; Segobin et al, 2014; Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic alcohol consumption has considerable neurotoxic effects, with the most pronounced damage reported in regions underpinning response inhibition, such as the frontal lobes and basal ganglia ( 21 23 ). In addition, the degree of brain atrophy is related to the amount of alcohol previously consumed ( 24 ). Hence, the deficit in preparatory suppression could be a consequence of brain damage induced by chronic alcohol exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence support this hypothesis. First, chronic alcohol consumption has important neurotoxic effects, with the most pronounced damage reported in regions underpinning impulse control, such as the frontal lobes and the basal ganglia ( Chanraud et al, 2007 , Fritz et al, 2019 ), and the degree of brain atrophy correlates with the amount of alcohol previously consumed ( Rolland et al, 2020 ). Moreover, we have shown that a weaker MEP suppression during action preparation was associated with a lower cortical thickness in medial frontal regions ( Quoilin et al, 2021 ), while patients suffering from a behavioral, substance-free, addiction, had a normal pattern of MEP suppression ( Quoilin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%